IDENTIFIKASI BAKTERI GRAM NEGATIF BATANG DAN GRAM POSITIF COCCUS PADA POTONGAN KUKU PEDAGANG AYAM POTONG DAN PEDAGANG DAGING SAPI DI PASAR GEDE HARDJONAGORO SURAKARTA - Ardy Prian Nirwana; Dinda Widyastuti; Febriana Valent Dika Putri; Nova Erlyta Puspitaningrum (LPPM Universitas Abdurrab, 2025)
Contamination of pathogenic bacteria in animal-based food products is a major cause of foodborne illnesses. This study aims to identify the presence of Gram- negative rods and Gram-positive cocci on fingernail clippings of poultry and beef traders at Pasar Gede Hardjonagoro, Surakarta. This descriptive observational study involved 20 samples, consisting of 10 poultry traders and 10 beef traders. Laboratory analysis included Gram staining, selective media isolation, and biochemical tests. The results showed that 18 out of 20 samples contained Gram- negative rods, while 2 samples contained Gram-positive cocci. The presence of these bacteria is strongly associated with poor personal hygiene practices, such as not washing hands with soap, not trimming nails regularly, and not using gloves while handling raw meat. These findings highlight the need for improved hygiene education and better sanitation measures in traditional markets to prevent the spread of foodborne pathogens